SAT0451 Disease course patterns in systemic lupus erythematosus. (12th June 2018) - Tselios, K.; Gladman, D.; Touma, Z.; Su, J.; Anderson, N.; Urowitz, M.
Abstract : Background: Previous studies described three patterns of disease activity over time in systemic lupus erythematosus (SLE), namely long quiescent, relapsing remitting and persistently active. However, they enrolled prevalent patients, many of whom in the late stages of the disease. As such, the patterns of disease course since diagnosis are not known. Objectives: The aim of the present study was to assess the prevalence and characteristics of such patterns over 10 years of follow-up in an inception cohort. Methods: The inception patients of a large lupus cohort (enrolled within 18 months of diagnosis, n=883), with at least 10 years of follow-up and no time interval >18 months between consecutive visits, were investigated. Monophasic (M) pattern was defined as a clinical SLEDAI-2K=0 [serology (anti-dsDNA antibodies and C3/C4 levels) excluded], achieved within five years since enrollment and maintained for ≥10 years after that. Relapsing-remitting (RR) pattern was defined based on ≥2 remission periods (a remission period equals two consecutive visits with a clinical SLEDAI-2K=0), while patients with no remission were categorised as persistently active (PA). Descriptive and regression analyses were used to compare the different groups regarding cumulative damage at 10 years, mortality and flare rate beyond 10 years. Results: Of 267 patients who fulfilled the inclusion criteria, 27 (10.1%) were monophasics, 180 (67.4%) RR and 25 (9.4%) PA. Thirty-five patients (13.1%) had only one remission period ("hybrid"). There were no significant differences regarding the demographic, clinical, immunological and therapeutic characteristics among groups at enrollment. At 10 years, PA patients had received significantly more glucocorticosteroids [39.4±24.3 g vs. 16.6±10.7 g and 27.3±18.4 g for the M and RR groups, p<0.001] and accumulated significantly more damage [SLICC/DI=2.36±1.6 vs. 0.93±1.07 and 1.22±1.33, respectively, p<0.001]. A trend for higher mortality was observed in the PA patients [24% vs. 13.3% and 11.1% for the RR and M patients respectively, p=0.22] whereas death occurred earlier [18.4±4.4 vs. 20.1±7.2 and 24±4.1 years, p=0.11]. Beyond 10 years, the annual flare rate was higher for the PA and RR patients as compared to the monophasics [0.50±0.40 vs. 0.47±0.57 vs. 0.10±0.18 respectively, p<0.001]. Multinomial regression analysis for group membership showed Black race [OR=2.78, 95%CI=1.05–7.31, p=0.039] and higher adjusted mean SLEDAI-2K over the first two years [OR=1.21, 95%CI=1.11–1.32, p<0.0001] to be associated with a more severe disease course. Conclusions: Approximately 70% of lupus patients followed a relapsing remitting course from diagnosis onwards, while 10% displayed a monophasic and another 10% a persistently active course. Black race and more severe disease over the first two years were associated with a worse disease course. Disclosure of Interest: K. Tselios: None declared, D. Gladman: None declared, Z. Touma: None declared, J. Su: None declared, N. Anderson: None declared, M. Urowitz Consultant for: Consultant GlaxoSmithKline